Media Pembelajaran Video Tutorial Berbasis Media Sosial Instagram Untuk Meningkatkan Hasil Belajar - Ita Prihatining Wilujeng; Sopiah Sopiah; Handri Dian Wahyudi (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Teachers should master various learning methods to improve students' understanding of the subject. The existence of online learning requires them to be able to convey material well to students without going through face-to-face activities and further explanations. Social media can be used in the learning process because it can save and share videos with students without needing to be downloaded and only requires a strong Internet network. One social media that can be used is Instagram that frequently accessed by students, this application can facilitate relationships with people in one direction or two directions, so it can attract and make it easier for students to access subject matter. In this community service implementation, the team provides training to vocational school’s teachers with lectures and questions and answers related to the use of this social media. As a result, teachers can master the Instagram social media application and understand the various features that are used in video tutorial learning media.